2021 Annual Scientific Meeting of the Nutrition Society of New Zealand Tūhono - Reconnecting - Brown, Rachel; Mackay, Sally; Eyles, Helen; Jalili-Moghaddam, Shabnam (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The annual scientific conference of the Nutrition Society of New Zealand was held virtually on the 2nd and 3rd December 2021. The aim of the annual conference is to foster discussion and disseminate the results of nutrition-related research. The conference also provides an opportunity for those working in practice to share their experiences and keep up to date with scientific advancements. The theme of the conference was 'Reconnecting - Tūhono'. One hundred and sixty-nine delegates attended over the two days. The programme comprised five plenary sessions, five concurrent oral sessions, and twenty-three short, prerecorded videos, with the latter serving as a replacement for the traditional poster format. Highlights of the five plenary sessions included presentations on food sovereignty by Dr Bevan Eruti and Christina McKerchar; women's health by Dr Megan Ogilvie and Dane Baker; sustainable diets by Dr Brent Clothier, Dr Nick Smith, and Dr Cristina Cleghorn; healthy environments for children by Jasmin Jackson; and the gut-brain axis and future foods by Dr Pramod Gopal, Tracey Bear, and Dr Jocelyn Eason. The Muriel Bell Lecture entitled 'Lick the plate clean: the intersection of food, nutrition, and waste' was presented by Professor Sheila Skeaff of the Department of Human Nutrition, University of Otago.